2019
DOI: 10.1038/s41416-019-0558-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating radiological response in pancreatic neuroendocrine tumours treated with sunitinib: comparison of Choi versus RECIST criteria (CRIPNET_ GETNE1504 study)

Abstract: BackgroundThe purpose of our study was to analyse the usefulness of Choi criteria versus RECIST in patients with pancreatic neuroendocrine tumours (PanNETs) treated with sunitinib.MethodA multicentre, prospective study was conducted in 10 Spanish centres. Computed tomographies, at least every 6 months, were centrally evaluated until tumour progression.ResultsOne hundred and seven patients were included. Median progression-free survival (PFS) by RECIST and Choi were 11.42 (95% confidence interval [CI], 9.7–15.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 35 publications
(50 reference statements)
0
17
0
Order By: Relevance
“…Each item was carefully selected to meet specific criteria: (1) to focus on the radiological findings most relevant for patient man- Subsequently, similar advantages of using modified RECIST criteria (mRECIST) for loco-regional therapy in NENs have been reported, in particular for the assessment of TACE of liver metastases. 5 In addition, it has been suggested that the CHOI criteria, initially developed for the assessment of gastrointestinal stromal tumors treated with Imatinib, may be appropriate for tumor response assessment in NENs treated with either targeted therapies such as sunitinib and everolimus [12][13][14] or peptide receptor radionuclide therapy. 15 Finally, the ADC, measured on diffusion-weighted MRI, has also become a promising quantitative biomarker for prediction and monitoring of the therapeutic response.…”
Section: Discussionmentioning
confidence: 99%
“…Each item was carefully selected to meet specific criteria: (1) to focus on the radiological findings most relevant for patient man- Subsequently, similar advantages of using modified RECIST criteria (mRECIST) for loco-regional therapy in NENs have been reported, in particular for the assessment of TACE of liver metastases. 5 In addition, it has been suggested that the CHOI criteria, initially developed for the assessment of gastrointestinal stromal tumors treated with Imatinib, may be appropriate for tumor response assessment in NENs treated with either targeted therapies such as sunitinib and everolimus [12][13][14] or peptide receptor radionuclide therapy. 15 Finally, the ADC, measured on diffusion-weighted MRI, has also become a promising quantitative biomarker for prediction and monitoring of the therapeutic response.…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, 3D volumetry of liver lesions has only been carried out within the framework of studies [ 51 , 52 ]. Besides the volumetric assessment of tumor burden, the 3D segmentations generated by the model presented in this study could be used for further lesion analysis, such as texture analysis, radiomics or contrast-uptake used in Choi criteria [ 53 , 54 ]. To date, most studies concerning artificial intelligence and liver imaging focus on diffuse liver disease or the classification of liver tumors [ 55 , 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…In interpreting the results, it is also important to note that the endpoint currently considered clinically relevant (i.e., PFS) depends on radiological progression according to morphological criteria (RECIST). This entails certain limitations in NENs, as functional differences are not factored in [18]. For its part, PFS is deemed an acceptable surrogate endpoint for OS in RCTs of NENs [53].…”
Section: Discussionmentioning
confidence: 99%
“…Patients initiated therapy between 2002 and 2017. The design, characteristics, and quality criteria of this registry have been previously reported [5,6,[16][17][18]. Data from a total of 4,068 available cases were screened for eligibility, and additional quality controls were implemented for this analysis (double-checking of data, monitoring of discrepancies, and unjustified missing data).…”
Section: Patientsmentioning
confidence: 99%